2022
DOI: 10.1088/1757-899x/1252/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the thermal properties of candle wax material

Abstract: Indoor air quality is a key aspect of people staying inside buildings. Combustion processes have been identified as one of the most important sources of pollutants in the indoor environment. Proper HVAC design must account for all sources and variations in their intensity, such as also the burning of candles, which produce not only increased amounts of carbon dioxide as a result of the combustion of the organic matrix, but also often dangerous organic substances. On the other hand, the candle burning represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…It can be concluded that the addition of essential oils lowering the melting point of the candle. Solid-liquid transition temperature of natural based candle reported lower than paraffin-based wax which palm stearin wax and paraffin wax had melting point at 50℃ and 60℃, respectively (Eštoková & Kapalo, 2022;Nusantoro, 2009). In addition, this mixture of wasted cooking oil (fatty acid) and palm stearin was in the range of melting point of palm stearin and paraffin wax.…”
Section: Melting Point and Burning Time Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…It can be concluded that the addition of essential oils lowering the melting point of the candle. Solid-liquid transition temperature of natural based candle reported lower than paraffin-based wax which palm stearin wax and paraffin wax had melting point at 50℃ and 60℃, respectively (Eštoková & Kapalo, 2022;Nusantoro, 2009). In addition, this mixture of wasted cooking oil (fatty acid) and palm stearin was in the range of melting point of palm stearin and paraffin wax.…”
Section: Melting Point and Burning Time Analysismentioning
confidence: 98%
“…This increases the urgency of changing material candles to be safer for humans and the environment. Natural waxes such as fatty acids and stearins can substitute the harm materials, which also had properties as phase change materials like paraffin wax (Eštoková & Kapalo, 2022). One of the famous fragrances of aromatherapy candles is orange essential oil.…”
Section: Introductionmentioning
confidence: 99%